Award dinner and super league - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
Last semester on April 2016, IMPRESS have been organized the first dinner outside from UMP premises which is a successful event for IMPRESS. It was held at Mandurah Hotel, Beserah with the theme Black and Rainbow.